Підвищення рівня фінансової грамотності та фінансової освіти - виклик сучасності - Латковська, Тамара Анатоліївна; Латковская, Тамара Анатольевна; Latkovskaja, Tamara (My University, 2013)
The questions of financial literacy and financial education, being to date actual and necessary, are examined in the article. Proved, that the insufficient possessing bases of financial knowledge and general information of citizens about the rights and duties is caused mistrust to financial institutions, unwillingness to use them as an instrument of providing of maintenance of economies and increase of level of welfare. Drawn conclusion about the necessity of system protection of financial rights and legal interests of wide layers of population, in conditioning for the increase of financial literacy and financial education, in creation of mechanisms of pre-trial decision of conflicts between the consumers of financial services and financial institutes.
Латковська Т. А. Підвищення рівня фінансової грамотності та фінансової освіти - виклик сучасності / Т. А. Латковська // Наукові праці Національного університету «Одеська юридична академія» : зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.), Ю. П. Аленін [та ін.] ; відпов. за вип. В. М. Дрьомін ; МОН України, НУ ОЮА. – Одеса : Юрид. л-ра, 2013. – Т. 13. – С. 429-438.
Keywords: фінансова грамотність; фінансова освіта; фінансове право; фінанси; фінансова система; захист прав споживачів; финансовая грамотность; финансовое образование; финансовое право; финансы; финансовая система; защита прав потребителей; financial literacy; financial education; financial right; finances; financial system; protection of consumers